2012
DOI: 10.1016/j.mayocp.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

ST Elevation Anterior “Spiked Helmet” Sign

Abstract: suggestive of ST-segment elevation myocardial infarction in patients who were found not to have ST-segment elevation myocardial infarction. 1 Typical of those cases were a critical illness, a unique dome-and-spike pattern always in the inferior leads, and high in-hospital mortality.We recently reported a case in which the "spiked helmet" sign appeared in the anteroapical leads ( Figure). 2 Coronary angiography excluded coronary artery disease as a cause of ST-segment elevation. The cause of death, as establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 2 publications
1
12
0
3
Order By: Relevance
“…In the original article and in subsequent publications, acute abdominal events such as ileus, bowel perforation, and gastric obstruction usually were associated with the spiked helmet pattern showing up in the inferior leads, whereas acute thoracic events such as aortic dissection, pneumothorax, and mechanical hyperventilation caused the spiked helmet sign in the chest leads. [2][3][4][5] Similar to the case of Hibbs et al, 1 normalization of the underlying noncardiac condition resulted in prompt resolution of the pseudo-ST-segment elevation. 5 We and others have hypothesized that the most likely cause of the spiked helmet sign was pulsatile epidermal stretch that occurred in concert with the cardiac cycle in the setting of an acute rise in intracavitary pressures.…”
Section: Correspondencementioning
confidence: 62%
See 2 more Smart Citations
“…In the original article and in subsequent publications, acute abdominal events such as ileus, bowel perforation, and gastric obstruction usually were associated with the spiked helmet pattern showing up in the inferior leads, whereas acute thoracic events such as aortic dissection, pneumothorax, and mechanical hyperventilation caused the spiked helmet sign in the chest leads. [2][3][4][5] Similar to the case of Hibbs et al, 1 normalization of the underlying noncardiac condition resulted in prompt resolution of the pseudo-ST-segment elevation. 5 We and others have hypothesized that the most likely cause of the spiked helmet sign was pulsatile epidermal stretch that occurred in concert with the cardiac cycle in the setting of an acute rise in intracavitary pressures.…”
Section: Correspondencementioning
confidence: 62%
“…5 We and others have hypothesized that the most likely cause of the spiked helmet sign was pulsatile epidermal stretch that occurred in concert with the cardiac cycle in the setting of an acute rise in intracavitary pressures. [2][3][4][5] In the case report by Hibbs et al also, the apparent ST-segment elevation seen in the lateral chest leads resembled the spiked helmet sign. An enlargement of leads V 3 through V 6 of their Figure 2 showed that the upright swing of the baseline started before the onset of the QRS complexes and therefore could not have reflected a true repolarization abnormality.…”
Section: Correspondencementioning
confidence: 83%
See 1 more Smart Citation
“…Several explanations for the appearance of this abnormal EKG findings include pulsatile contraction of the diaphragm in sync with the cardiac cycle [4,5] and other mechanisms of diaphragmatic activities including abnormal breathing patterns with unexplained respiratory artifacts [6] or repetitive epidermal stretch due to acute increase in intra-abdominal or intrathoracic pressures [7,8]. These findings often indicate the need to rule out acutely evolving events in the chest or the abdomen [9]. These EKG findings have also been known to commonly occur in the inferior leads and in which case, may point strongly to an acute abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…These EKG findings have also been known to commonly occur in the inferior leads and in which case, may point strongly to an acute abdomen. Additionally, the presence of these EKG findings in the precordial leads may be more suggestive of acute rise in intrathoracic pressure with causes such as an aortic dissection, pneumothorax, pneumomediastinum or acute respiratory distress syndrome [7,8,9,10]. A link between phrenic nerve stimulation and the baroreceptor reflex has also been suggested to play a role in the presence of synchrony between diaphragmatic contractions and ventricular contractions [5].…”
Section: Discussionmentioning
confidence: 99%